Ecosystem services and tree plantations in Uruguay: A reply to Vihervaara et al. (2012) - Paruelo, José (2012)
The expansion of industrial tree plantations in South America is a case of land transformation that has already generated conflicts at the local, national and international levels. In a recent article, Vihervaara et al. (2012) present a controversial analysis, mainly for the potential use of some of their results; they suggest that the general attitude among the local people toward an increment in tree plantations and toward the forest industry is positive. In this article I discuss the results and conclusions of the Vihervaara et al. article, particularly those related to the definition of the ecosystem services concept, the definition of stakeholders and the approaches to deriving their perception, and the available evidence on the impacts of grassland afforestation in Uruguay.